Degenerative tendoachilles tear repaired and augumented by peroneous brevis tendon by dynamic loop technique one year follow up - Reddy, K. Vijaya Bhaskar; Lavudi, Narsimha (International Journal of Research in Orthopaedics, 2020)
Background: Repair of degenerative rupture of tendoachilles is a challenge for orthopaedician. We used peroneus brevis tendon in our patients to augment the repair of degenerated tendoachilles tears by creating a dynamic loop. Methods: In our study, we evaluated 31 patients with Achilles tendon rupture treated by reconstruction using peroneus brevis tendon transfer by dynamic loop suture technique. The patients were from all age groups excluding those lesser than 35 years. The average follow-up being 6 months. Results: In total 31 patient’s majority of patients belong to 41-50 years (15 cases 48.4%). Male patients being 24 (77.4%) constituted the majority, right sided injury was noted in 23 (74.2%) of the patients. Most common symptom of Achilles tendon rupture is pain. The mechanism of injury in most of the patients by stumbling in the fields in 19 (61.3%). Results of testing the patient’s ability to heel raise for 60 seconds 20 patients were able to sustain, while 8 patients were able to stand on toe with heel raised but could not sustain it. 3 patients could not do raise the heel. 5 patients complained of sensory hypoesthesia at 12 months follow-up. By Rupp scoring, 77% patients had excellent or good results and 10% had fair or poor results. Conclusions: Results of reconstruction of Achilles tendon ruptures using peroneus brevis tendon show a strong and stable repair that allows early weightbearing ambulation with favourable clinical results in most patients.